A study to correlate serum pseudocholinesterase and serum creatine phosphokinase levels in acute organophosphorus poisoning with respect to Peradeniya organophosphorus poisoning scale - K., Yaduraj D.; K., Sahana; S., Sheshan V.; M., Pramila; R., Madhumathi (International Journal of Advances in Medicine, 2022)
Background: Organophosphorus insecticides are one of the most common causes of poisoning in India. It has a high mortality rate and accounts for a third of suicidal deaths in south-east Asia. Methods: The objectives were to estimate serum pseudocholinesterase and creatine phosphokinase (CPK) levels in organophosphorus poisoning and correlate them with the severity and prognosis described by the Peradeniya organophosphorus poisoning (POP) scale at initial presentation. This was a cross-sectional study conducted over 18 months. A total of 180 organophosphorus-poisoning subjects were divided into mild, moderate and severe grades based on POP scale at admission. Serum pseudocholinesterase and CPK levels were estimated at admission. The outcome was noted, and the results were statistically analysed. Results: It was found that 112 (62.2%), 51 (28.3%) and 17 (9.4%) patients had mild, moderate and severe poisoning, respectively, according to POP scale. Mean pseudocholinesterase level (units/litre) was 2393.29, 1104.37 and 638.18 and mean serum CPK level (units/ litre) was 153.41, 344.94 and 280.53 in mild, moderate and severe poisoning, respectively. ICU and ventilator were required for 84 (46.75%) and 72 (40%) patients, respectively. Mortality was 17.8%. Negative, weak and significant correlation was seen between POP score and pseudocholinesterase (r=-0.265, p=0.00). Positive, moderate and significant correlation was seen between POP score and CPK levels (r=0.449, p=0.00). Conclusions: POP scale applied at admission along with serum pseudocholinesterase and CPK levels serve as a simple and effective system to determine early need for ventilation and mortality in rural, peripheral centres in developing nations.